Analisis Substansi Undang-Undang Nomor 23 Tahun 2014 tentang Pengalihan Urusan Kehutanan dari Pemerintah Kabupaten/Kota kepada Pemerintah Provinsi - Pramesti, Fadia; Nurhadi, Salma Putri; Tanjung, Nurul Fitralaila (As-Syirkah: Islamic Economic & Financial Journal, 2023)
With the enactment of Law concerning Regional Government Number 23 of 2014, it is clear that the provincial government has begun to pay greater attention to the forestry sector. This is because the authority granted allows the provincial government to coordinate and manage all aspects of forestry in all districts/cities. This research aims to find out and analyze the substance of Law Number 23 of 2014 concerning the transfer of forestry affairs from district/city governments to provincial governments. The method used is a literature study, where various previous studies are collected to answer various problems regarding regional government authority in forestry matters. The research results show that the substance of Law Number 23 of 2014 eliminates the technical authority that regions, especially districts/cities, have in controlling natural resources, including forestry matters involving various regions. All cross-regional natural resources are the full responsibility of the provincial government or above level. This causes the position of district/city government officials to become limited. The implementation of Law Number 23 of 2014 has also apparently not been completely successful in overcoming existing problems, but this has actually increased the complexity of relations between the center and the regions.